Dynamics of the immediate behavioral response to partial social exclusion - Dewald-Kaufmann, Julia F.; Wüstenberg, Torsten (Scientific reports, 2021)
Social rejection and exclusion (ostracism) represent main stressors in daily life and even threaten mental and physical health. Abundant data from subjective measures in social exclusion paradigms are available, but the dynamic behavioral response is largely unexplored. Here, we applied modified variants of the Cyberball paradigm in two consecutive experiments to investigate the adaptive behavioral and emotional reactions to partial social exclusion. In experiment 1, 68 healthy participants (females, mean age 24.76 ± 4.05 years) played 2 min inclusion, 5 min partial exclusion and 2 min total exclusion. In experiment 2, 94 healthy participants (48 females, mean age 34.50 ± 12.08 years) underwent an experimental condition (2 min inclusion, 10 min partial exclusion) and a control condition (12 min inclusion only) in randomized order. In experiment 1, behavioral responses to partial exclusion showed two characteristics: (1) an immediate increase in ball passes to the excluding player followed (2) by a later return of participants’ behavior to baseline. This finding was replicated for both genders and in comparison to a control condition in experiment 2. The dynamic behavioral response observed here may point to overlapping principles of cooperation in this ball tossing paradigm and serves as a novel experimental proxy.
Gesehen am 04.03.2021